Development of Multiplex qPCR Method for Accurate Detection of Enzyme-Producing Psychrotrophic Bacteria - Kidane Yalew; Shuwen Zhang; Solomon Gebreyowhans; Ning Xie; Yunna Wang; Jiaping Lv; Xu Li; Xiaoyang Pang (Foods)
Microbial detection in milk is crucial for food safety and quality, as beneficial and harmful microorganisms can affect consumer health and dairy product integrity. Identifying and quantifying these microorganisms helps prevent contamination and spoilage. The study employs advanced molecular techniques to detect and quantify the genomic DNA for the target hydrolytic enzyme coding genes lipA and aprX based on the multi-align sequence conserved region, specific primer pair, and hydrolysis probes designed using the singleplex qPCR and multiplex qPCR. Cultured isolates and artificially contaminated sterilized ultra-high-temperature (UHT) milk were analyzed for their specificity, cross-reactivity, and sensitivity. The finding indicated that strains with lipA and aprX genes were amplified while the other strains were not amplified. This indicated that the designed primer pairs/probes were very specific to the target gene of interest. The specificity of each design primer pair was checked using SYBR Green qPCR using 16 different isolate strains from the milk sample. The quantification specificity of each strain target gene was deemed to be with a mean Ct value for positive pseudomonas strain > 16.98 ± 1.76 (p < 0.0001), non-pseudomonas positive strain ≥ 27.47 ± 1.25 (p < 0.0001), no Ct for the negative control and molecular grade water. The sensitivity limit of detection (LOD) analyzed based on culture broth and milk sample was >105 and >104 in PCR amplification while it was >104 and >103 in real-time qPCR, respectively. At the same time, the correlation regression coefficient of the standard curve based on the pure culture cell DNA as the DNA concentration serially diluted (20 ng/µL to 0.0002 ng/µL) was obtained in multiplex without interference and cross-reactivity, yielding R2 ≥ 0.9908 slope (−3.2591) and intercepting with a value of 37, where the efficiency reached the level of 95–102% sensitivity reached up to 0.0002 ng/µL concentration of DNA, and sensitivity of microbial load was up to 1.2 × 102 CFU/mL. Therefore, multiplex TaqMan qPCR simultaneous amplification was considered the best method developed for the detection of the lipA and aprX genes in a single tube. This will result in developing future simultaneous (three- to four-gene) detection of spoilage psychrotrophic bacteria in raw milk.